Kamishoyosan Alleviates Anxiety-like Behavior in a Premenstrual Syndrome Rat Model. (14th October 2022) - Iba-Tanaka, Hikari; Watanabe, Takuya; Harada, Kyoka; Kubota, Kaori; Katsurabayashi, Shutaro; Iwasaki, Katsunori
Abstract : Kamishoyosan (KSS) is a traditional Japanese Kampo medicine that is prescribed for hormonal change-induced mood disorders including premenstrual syndrome (PMS). In clinical studies, KSS exhibited ameliorative effects on mood symptoms of PMS, such as anxiety and irritability. However, the mechanism underlying the beneficial effects of KSS is unclear. In the present study, we investigated the involvement of serotonergic machinery in the anxiolytic effects of KSS on hormonally-induced anxiety-like behavior in progesterone withdrawal (PWD) rats, which were used as a model of PMS. Female rats were injected with progesterone daily for 21 days. At 48 h after the final progesterone injection, anxiety-like behavior was evaluated using the elevated plus maze. KSS was administered orally to PWD rats 1 h prior to the test and significantly attenuated PWD-induced anxiety-like behavior. This ameliorative effect of KSS was reversed by WAY-100635, a serotonin (5-HT)1A receptor antagonist. The effect of KSS on serotonergic transmission in the prefrontal cortex of PWD rats was also evaluated using an in vivo microdialysis procedure. KSS significantly increased the extracellular 5-HT level in the prefrontal cortex of PWD rats. In conclusion, our results suggest that KSS alleviates PWD-induced anxiety-like behavior at least partly by activating 5-HT1A receptors and enhancing serotonergic transmission.